Driving forces behind informal sanctions - Armin Falk; Ernst Fehr; Urs Fischbacher (Institute for the Study of Labor (IZA), 2005)
This paper investigates the driving forces behind informal sanctions in cooperation games and the extent to which theories of fairness and reciprocity capture these forces. We find that cooperators' punishment is almost exclusively targeted towards the defectors but the latter also impose a considerable amount of spiteful punishment on the cooperators. However, spiteful punishment vanishes if the punishers can no longer affect the payoff differences between themselves and the punished individual, whereas the cooperators even increase the resources devoted to punishment in this case. Our data also discriminate between different fairness principles. Fairness theories that are based on the assumption that players compare their own payoff to the group's average or the group's total payoff cannot explain the fact that cooperators target their punishment at the defectors. Fairness theories assuming that players aim to minimize payoff inequalities cannot explain the fact that cooperators punish defectors even if payoff inequalities cannot be reduced. Therefore, retaliation, i.e., the desire to harm those who committed unfair acts, seems to be the most important motive behind fairness-driven informal sanctions.
Keywords: A13; D63; D23; C92; K42; 330; sanctioning; cooperation; social norm; reciprocity; fairness; spitefulness; Kooperatives Spiel; Gerechtigkeit; Strafe; Test; Theorie; Soziale Norm